KELAYAKAN FINANSIAL USATANI KEDELAI - Dedi Djuliansah; Trisna Insan Noor; Yosini Deliana; Meddy Rachmadi (Universitas Galuh Ciamis, 2019)
This study aims to identify the cost, revenue, and income of soybean farming, identify the feasibility of soybean farming, identify the breakeven point and change the break-even point due to changes in selling prices in Jatiwaras District, Tasikmalaya Regency. The method used in this study is a survey method, while the data used consists of primary data and secondary data. Determination of sample farmers using the Two Stage Cluster Random Sampling method, with a sample size of 65 people with a proportion of 27 farmers in paddy fields and 38 farmers in land, from a population of soybean farmers as many as 185 people. The results of this study indicate that the cost of soybean farming per hectare in paddy fields is Rp. 5,896,896.90 with receipts of Rp 8,478,139.53 and income of Rp. 2,581,242.63, while the cost of soybean farming per hectare on land is Rp. 4,163,487.48 with receipts of 8,342,774.57 and income of Rp. 4,179,287.09. Soybean farming in land is more feasible to be cultivated with an R / C value of 2.01 while the R / C value in paddy fields is 1.45. Minimum acceptance received by farmers from soybean farming so as not to lose in one planting season of Rp. 63,911.14 in paddy fields and Rp. 668,378.02 in land, the minimum production volume received by farmers from soybean farming so as not to lose in one planting season is 10.65 Kg in paddy fields and 111.40 Kg in land and minimum land area that must be processed by farmers so that no loss in one planting season of 0.01 ha in paddy fields and 0.08 ha on land. Decrease in output price of Rp. 1,000.00 (16.67%) causes the minimum acceptance received by farmers from soybean farming so as not to lose in one planting season of Rp. 100,196.38 in paddy fields and Rp. 767,384.61 on land. The margin value of safety on soybean farming is 90.53 in wetland and 82.40 in land area